Live weight and sex effects on carcass and meat quality of "Borrego terrincho-PDO" suckling lambs - Santos, Virgínia (2007)
Fifty seven suckling lambs (28 males and 29 females) of the Churra da Terra Quente breed were used to evaluate the effects of live weight and sex on carcass composition and meat quality traits. Lambs were slaughtered at three weight classes (< 8 kg, 8-11 kg and > 11 kg) according to "Borrego Terrincho-PDO" specifications. The left sides of the carcasses were totally dissected. The longissimus thoracis and lumborum muscle was used for meat quality determination. Dressing proportion and carcass fatness were not affected by weight class or sex. Muscle proportion was similar in all carcass joints for the three weight classes. The percentage of bone decreased at the higher weight class, while that of subcutaneous and intermuscular fat increased. Female lambs had higher muscle proportions and greater muscle/bone ratios in the carcass side than males. Muscle pH, colour, cooking losses and tenderness were not affected by gender and weight class. Female lambs and weight classes 8-11 kg and >1 I kg had higher proportions of intramuscular fat.